A brief history of the development of blasting and the modern theory of rock breaking - A K Kirsanov; S A Vokhmin; G S Kurchin (Brawijaya University, 2016)
The article is devoted to the task today to improve the effectiveness of blasting during construction of horizontal and inclined mine excavations. Construction of new and reconstruction of existing mines requires large volume of excavation works, which length can reach tens of kilometers for only one project. Drilling and blasting workings allow not only to break out rocks from a frontal part of an excavation, but also cause an internal effect, which can lead to undesired damage that, in turn, often lead to increased expenses for excavation operations and safety problems for personnel. Calculation methods for blasting and explosion operations is a topical issue in mining industry as they allow to improve characteristics of excavation works and safety of explosion operations. Dozens of scientists offer their design, which reflects the vision of the problem and its solution. There are many methods for calculating the parameters of drilling and blasting, but so far not developed a uniform methodology of calculation, which would encompass all the factors and explained the mechanism of formation of cracks around the explosive charge and the process of breaking rock. The paper presents a novel methodology for calculations for blasting and explosion operations. That methodology comprises various specifics of rock geology and mining engineering during works in horizontal and vertical excavations. In this paper given an algorithm for calculation two main areas of destruction: crushed zone and fracturing zone. In addition, article outlines main aspects of Mining Engineering Development from Antiquity until present days and presents the dynamic of mineral resources.